THE SYSTEM OF COUNTERACTION TO UNMANNED AERIAL VEHICLES - Lishchyna, Nataliia; Lishchyna, Valerii; Povstiana, Yuliia; Yashchuk, Andrii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
In the article, the development of a system of counteraction to unmanned aerial vehicles is considered. A way to counteract unmanned aerial vehicles is described. The analysis of parameters of the system and its constituent parts is carried out. The structural scheme of the system, functional and principle schemes of subsystems on the basis of Arduino are described.